Many manifestations of digestive ripening: monodispersity, superlattices and nanomachining - Sidhaye, Deepti S.; Bhagavatula L. V. Prasad (New Journal of Chemistry, 2011)
Digestive ripening has now been established as a very convenient route to obtain monodisperse nanoparticles from polydisperse ones by refluxing the latter in the presence of an excess ligand. Many ligands including long chain thiols, amines, or phosphines have been shown to be effective digestive ripening agents. It is hypothesized that the surface active groups of such digestive ripening agents bind and remove reactive surface atoms/clusters from big nanoparticles and redeposit them on smaller nanoparticles. In this way, large particles become smaller, while small particles become larger, and eventually, an equilibrium size is obtained that is specific to each of the digestive ripening agents used. Herein, the digestive ripening procedure is reviewed, discussed and its utility spanning the preparation of monodispersed metal nanoparticles, alloy nanoparticles, superlattice structures and the most interesting nano-machining (wherein the monodisperse particles can be reverted back to the polydisperse system) is demonstrated.